Consumers’ Perception of Prices on English Food Menu - Haratikka, Haya; Sony, Rapat Piter (English Study Program, Faculty of Teacher Training and Educational Sciences, Universitas Timor, 2022)
Nowadays, the use of English language becomes popular. It spreads to all life aspect, especially in cafe/restaurant business. The cafe/restaurant owners used English as written on the menu list. This was an experimental research, 25 respondents as the control group and 25 respondents as the experience group. This research was going to investigate whether the use of English language in the food and drink menu give a significant effect for the business profit. The data of this research was taken from 25 respondents of STIE Bina Karya’s students who has ordered from the cafe/restaurant whose menu written in English language. Then, the data were analyzed quantitatively from the result of the google-survey distribution. As the result, from the price indicators, it showed that consumers did't mind with the higher prices at restaurants/cafe with English language menus they offer. Therefore, the businessmen were suggested to use English language as written on their menu list.